1973
DOI: 10.1139/f73-324
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Fishery Potentials of Lakes and Reservoirs

Abstract: Timeliness in estimating fishery potentials seems more important than precision, at least in the earlier periods of development of specific fisheries. Comparative studies of several sets of lakes, particularly of those supporting developing fisheries in Africa, suggest that potential yield may be related to several simple indices of production. The morphoedaphic index, derived from measures of total dissolved solids and the mean depth, has provided the simplest and most general approach to the problem of initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…The rapid response of these riverine fishes corresponds with previous evidence from tropical systems (Agostinho et al, 2016, ; Cottet et al, ; Henderson, Ryder, & Kudhongania, 1; Williams, Winemiller, Taphorn, & Balbas, ) and fits the general expectation of Turgeon et al () with fish populations in this tropical reservoir peaking considerably faster (0.9–1.4 years) than temperate (4.1 years) and boreal (4.5 years) systems. Although the short fill time (4 months) was clearly an important factor, the quick ecological response was primarily a consequence of the higher productivity of warm‐water ecosystems (Brown, Gillooly, Allen, Savage, & West, ; Lowe‐McConnell ).…”
Section: Discussionsupporting
confidence: 87%
“…The rapid response of these riverine fishes corresponds with previous evidence from tropical systems (Agostinho et al, 2016, ; Cottet et al, ; Henderson, Ryder, & Kudhongania, 1; Williams, Winemiller, Taphorn, & Balbas, ) and fits the general expectation of Turgeon et al () with fish populations in this tropical reservoir peaking considerably faster (0.9–1.4 years) than temperate (4.1 years) and boreal (4.5 years) systems. Although the short fill time (4 months) was clearly an important factor, the quick ecological response was primarily a consequence of the higher productivity of warm‐water ecosystems (Brown, Gillooly, Allen, Savage, & West, ; Lowe‐McConnell ).…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, indirect evidence from commercial and recreational fisheries landings and knowledge of tropical reservoirs suggest that the duration of the trophic surge can be relatively short (2–10 yr; Henderson et al. , Balon and Coche , Williams et al. , Agostinho et al.…”
Section: Discussionmentioning
confidence: 99%
“…Also Henderson et al (1973) found for the simpler, pelagic ecosystem of Lake Tanganyika that 80% of the variance in clupeid abundance was due to the predatory Lares spp. (Centropomidae), while fishing effort and clupeid abundance showed no significant correlation.…”
Section: Management Of Ecosystems With Biological Interactionmentioning
confidence: 99%